Mohammad Natsir Islamic Education Concept And Their Relavance In Islamic Education Curriculum: Konsep Pendidikan Islam Mohammad Natsir Dan Relavansinya Dalam Kurikulum Pendidikan Islam - Mohammad Irva' Uddarojatur Rohman; Budi Hariyanto (Academia Open, 2022)
The purpose of this research is to find out about the concept of Islamic Education Mohammad Natsir. This type of research uses library research, for the method used in this research is to use the method of analysis or analysis. The results of the study found that the concept of Mohammad Natsir that he wanted was an education that combined general education with religion. This continuity was proven by the integral concept of Mohammad Natsir which did not distinguish between eastern education and western education. Because Islam does not equate rights with falsehood. All rights can be received or from the west, and all that has a false nature will be removed even though it also comes from the east. Because Islam has never known fanaticism as long as it is beneficial to humans and does not violate the law of its religion, then this pattern is based on creating students who care about their spiritual and physical bodies. so as not to forget the creator. From these concepts and rationale as for their relevance in education to develop Islamic education curriculum at this time.